2017
DOI: 10.1051/0004-6361/201630286
|View full text |Cite
|
Sign up to set email alerts
|

Decay of COSAC and Ptolemy mass spectra at comet 67P/Churyumov-Gerasimenko

Abstract: Context. The Rosetta lander Philae successfully landed on the nucleus of comet 67P/Churyumov-Gerasimenko on 12 November 2014. Philae is equipped with two gas analyzers: The Cometary Sampling and Composition experiment (COSAC) and the gas chromatograph and mass spectrometer Ptolemy. Aims. COSAC is designed for in situ analysis of organic molecules on 67P while Ptolemy is optimised to measure ratios of stable isotopes. Methods. On 12 to 14 November 2014 both instruments measured the organic composition of the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Shortly after Philae's first touchdown, first Ptolemy and then COSAC performed preprogrammed measurement sequences in their sniff modes (Ulamec et al 2016); they sampled cometary material most probably ejected from the Agilkia site during the touchdown, providing the first ever mass spectra so close to a comet (Goesmann et al 2015;Wright et al 2015). Further measurements were made; however, these initial spectra were noted to have the highest intensities and a number of peaks (Goesmann et al 2015;Krüger et al 2017) for the entire science operation period of Philae from 2014 November 12 to 15.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after Philae's first touchdown, first Ptolemy and then COSAC performed preprogrammed measurement sequences in their sniff modes (Ulamec et al 2016); they sampled cometary material most probably ejected from the Agilkia site during the touchdown, providing the first ever mass spectra so close to a comet (Goesmann et al 2015;Wright et al 2015). Further measurements were made; however, these initial spectra were noted to have the highest intensities and a number of peaks (Goesmann et al 2015;Krüger et al 2017) for the entire science operation period of Philae from 2014 November 12 to 15.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the COSAC measurements the peak at m/z 44 decays much slower than all the other ion species, including the water peak and, the m/z 44 peak also decays much slower in the COSAC measurements than in the Ptolemy data. From these results, it has been concluded that COSAC analysed a regolith sample from the cometary nucleus in situ while Ptolemy measured cometary gas from the ambient coma [7].…”
Section: Detection Of Organic Molecules On the Comet Surface-cosac Mamentioning
confidence: 95%
“…Nonetheless, a precious few measurements were made with the lander including those from the two distinct MS instruments: COSAC and PTOLEMY. COSAC's mission objective aimed to study both the chemical composition and isotopic abundance of volatiles in the cometary atmosphere and from samples collected from the surface (Rosenbauer et al, 1999;Goesmann et al, 2007Goesmann et al, , 2014Krüger et al, 2017). To do so, it utilized a GC-coupled to a multipass TOF instrument with a mass range from 1 to 1500 m/z, as described in detail by Goesmann et al (2006) Originally the multipass TOF design was proposed with either a figure-of-eight geometry or a clover-leaf geometry (Rosenbauer et al, 1999) but was later changed to a linear gridless reflectron configuration.…”
Section: Philae Landermentioning
confidence: 99%